The Effect of Foliar Application of Gibberellin and Kinetin Hormones on Morphological, Biochemical and Functional Characteristics of Maize (Zea mays L.) Hybrids - Aghil Aalipour; Tayeb Saki Nejad; Shahram Lak; Alireza Shokuhfar; Mojtaba Alavifazel (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In agronomic management of corn, in addition to providing suitable hybrid seeds, other factors such as plant hormones are also important. Therefore, this study was conducted to investigate the effect of hybrid seed type and leaf application of gibberellin and kinetin hormones on growth, biochemical and yield indices of corn in Ahvaz. The basic design of randomized complete blocks was done as a split plot in two cropping years with four replications. Single-grain corn hybrids 704 (late ripening), 616 (medium ripening) and 71AS (medium ripening) were studied as the main factor and kinetin/gibberellin foliar application at three levels of 0, 150/200 and 300/400 ppm as the secondary factor. The results showed that the simple effect of hybrid type and kinetin/gibberellin foliar application on plant height, stem diameter, shoot dry weight, 1000-seed weight, biological yield, grain yield, harvest index, chlorophylls a, b and total and the percentage of grain protein was statistically significant. Also, the effect of kinetin/gibberellin foliar application × hybrids on plant height, stem diameter, shoot dry weight, 1000-seed weight, biological yield, grain yield, harvest index, chlorophylls a, b and total and hybrid interaction in kinetin/gibberellin foliar application had a statistically significant effect on leaf area index per year. The results showed that the highest values of the studied traits in both cropping years were obtained in single cross 704 maize and after kinetin/gibberellin foliar application at 150-200 ppm. The kinetin/gibberellin ratio of 150/200 ppm in all hybrids had a better effect on various morphological and biochemical traits. The highest biological yield, grain yield and harvest index, which are very important traits, were related to single-cross corn hybrid with hormone foliar application at the rate of 150/200 ppm. According to the obtained results, the use of single-cross corn hybrid of corn and foliar application of maize plants with gibberellin and quinine in the ratio of 150/200 ppm is recommended.